Theory building in developmental psychology - Geert, Paul van (Advances in psychology (Amsterdam, Netherlands), 1986)
Discussing (from various viewpoints) problems in theory building and theory evaluation, this book starts from the assumption that theories of development are particular ways of defining the concept of psychological development in terms of a specific conceptual framework, as well as in terms of a specific empirical range (nature of the explained phenomena, prototypical experiments and applications, etc.). The first three parts deal with basic problems in modern developmental psychology, namely ways of describing development and how they direct theory formation; causes and conditions of developme.